Venous thromboembolism in adults screened for Sickle Cell Trait: a population based cohort study with nested case-control analysis - Little, Iain; Vinogradova, Yana; Orton, Elizabeth; Kai, Joe; Qureshi, Nadeem (BMJ Publishing Group Ltd, 2017)
Objective: To determine whether sickle cell carriers (‘sickle cell trait’) have an increased risk of venous thromboembolism (VTE).